Avaliação das atividades hipoglicemiante e hipolipidêmica da mistura de α,β-amirina, triteroenos pentacíclicos isolados do Protium heptaphyllum, em camundongos - Frota, Julyanne Torres (2011)
The Protium heptaphyllum (almecegueira) exudes an amorphous resin consisting of four binary mixtures of triterpenoids, and the mixture of ,-amyrin its major constituent. In folk medicine, the resin of Protium heptaphyllum is used as anti-inflammatory, gastroprotective, analgesic, expectorant and healing. The mixture of pentacyclic triterpenes ,-amyrin (AB) (63:37) has gastroprotective, antipruritic, antiinflammatory and antioxidant properties. Experimental studies with pentacyclic triterpene compounds belonging to the groups ursan, oleanan and lupan showed inhibition of different enzyme systems intimately related to metabolism/absorption of carbohydrates and lipids. Thus the hypoglycemic and hypolipidemic activity of AB was evaluated in Swiss mice, the models of diabetes induced by streptozotocin (STZ) and alloxan (ALX) and hyperlipidemia induced by triton WR-1339 and hyperlipidemic diet (DH). AB (10, 30 and 100mg/kg) was able to reduce blood glucose in a model of acute treatment in STZ-induced diabetes, we observed two times (3 and 5 hours after administration of AB). In five days after treatment of diabetic animals by ALX, AB (30 and 100 mg/kg) also decreased hyperglycemia, an effect also observed for the use of glibenclamide (10 mg/Kg) in both models. But in normal animals, AB did not affect blood glucose, unlike the positive control glibenclamide (10 mg/kg). Although the model of diabetes for ALX, AB reduced total cholesterol (TC) serum at a dose of 100mg/kg, and triglycerides (TG) at doses of 30 and 100 mg/kg. In this same model, reduced the serum amylase AB (AB 30 and 100 mg/kg) and serum lipase (AB 100 mg/kg), a result also observed in normal animals, the same doses. In the Oral Glucose Tolerance Test (OGTT), AB (30 and 100 mg/kg) was shown to reduce blood glucose levels 60 min after administration of glucose, and AB (10, 30 and 100 mg/kg) in 90 min. In the model of hyperlipidemia by triton, AB (10, 30 and 100 mg/kg) significantly reduced the levels of TC and TG, in times of 24 and 48 h after administration of triton, an effect also observed for fenofibrate (200 mg/kg) used as positive control. The levels of HDL-c elevation experienced with the use of AB at all doses and times observed, as well as fenofibrate. In the model of hyperlipidemia by HD, AB (10, 30 and 100 mg/kg) controlled weight gain of animals receiving HD, as well as reduced TC, TG, LDL-c and VLDL-c, although the latter only in doses 30 and 100 mg/kg. These two doses were also effective in raising HDL-c. All doses of AB administered reduced the atherogenic index. All doses of AB also reduced the hepatic cholesterol in this model. All effects reported were similar to the positive control (fenofibrate 200 mg/kg). AB (10, 30 and 100 mg/kg) was able to significantly improve the antioxidant defenses of the liver, because it elevated the activity of hepatic SOD and CAT when compared to control high-fat diet, and raised the level of NP-SH in dose of 100 mg/kg, as well as reduced lipid peroxidation by decreasing the MDA, at all doses. Together, these results indicate that α,β-amyrin has hypolipidemic and hypoglycemic effect and deserves further evaluation in larger animal models that simulate chronic conditions of diabetes and dyslipidemia, in addition to research on their mechanism of action.